Effects of Organizational Silence on Organizational Citizenship Behaviors: The Mediating Role of Positive Leadership Behaviors - Abbas Babaeinejad; Khashayar Setoodeh; Mohammad Dehyadegari; Hoda Sadat Shahamat (Iranian Journal of Educational Research)
Objective: The principal aim of this inquiry was to clarify the effects of organizational silence on the organizational citizenship behaviors exhibited by employees, with a particular focus on the mediating role of positive leadership behaviors. Methods: A sample of 280 employees drawn from both governmental and non-governmental entities situated in Kerman, Iran, selected through accessible sampling techniques. The collection of data was conducted through the implementation of the Organizational Silence Questionnaire, the Organizational Citizenship Behaviors Scale, and the Positive Leadership Behaviors Questionnaire. Structural equation modeling (SEM) was employed to investigate the mediating function of positive leadership behaviors in the association between organizational silence and organizational citizenship behaviors, while the bootstrap method was applied to evaluate indirect effects. Results: The results indicated that the hypothesized model exhibited an adequate fit with the empirical data (CFI = 0.91, RMSEA = 0.062). Specifically, the findings demonstrated a negative and statistically significant relationship between organizational silence and organizational citizenship behaviors (r = -0.43, p < 0.01), a negative and statistically significant relationship between organizational silence and positive leadership behaviors (r = -0.51, p < 0.01), and a positive and statistically significant relationship between positive leadership behaviors and organizational citizenship behaviors (r = 0.48, p < 0.01). The analysis conducted through structural equation modeling validated that positive leadership behaviors act as a mediator in the relationship linking organizational silence to organizational citizenship behaviors among employees, revealing a significant indirect effect (β = -0.24, p < 0.01). Conclusions: These results imply that strategies aimed at fostering both positive leadership behaviors and organizational citizenship behaviors may be effective in mitigating employees' organizational silence.